PENGARUH KEPERCAYAAN KONSUMEN, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI FLAMINGGO COLLECTION - Azalia Calvina Octavia (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study is to determine the effect of consumer trust, product quality, and price perceptions on purchasing decisions at the Flaminggo Collection. The Analysis technique of this research was conducted using component-based SEM method using Partial Least Square approach. The basis used for hypothesis testing on PLS is resampling with bootest strapping developed by Geisser and Stone. The variable are Consumer trust (X1), Product quality (X2), Price perception (X3), and Purchase Decision (Y). The primary data in this study was by distributing questionnaires to flaminggo collection consumers. It involved 60 respondents with aged 16-33 years. Secondary data used in this study is data obtained from Flaminggo Collection for the last 6 years (2014-2020). The results of the analysis show that Consumer Trust can play an important role in Purchasing Decisions at the Flaminggo Collection because the higher consumer trust, the higher the purchasing decision at the clothing store. Product quality can play an important role in the Flaminggo Collection because the higher the quality of the product, the higher the purchasing decision at the clothing shop. Price perception can play an important role in purchasing decisions at the Flaminggo Collection because the higher the price perception, the higher the purchasing decision at the clothing store. Keywords: consumer trust, product quality, price perception, and purchase decision.